Nowcasting East German GDP growth: A MIDAS approach - Jo\~ao C. Claudio; Katja Heinisch; Oliver Holtemöller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
Economic forecasts are an important element of rational economic policy both on the federal and on the local or regional level. Solid budgetary plans for government expenditures and revenues rely on efficient macroeconomic projections. However, official data on quarterly regional GDP in Germany are not available, and hence, regional GDP forecasts do not play an important role in public budget planning. We provide a new quarterly time series for East German GDP and develop a forecasting approach for East German GDP that takes data availability in real time and regional economic indicators into account. Overall, we find that mixed-data sampling model forecasts for East German GDP in combination with model averaging outperform regional forecast models that only rely on aggregate national information.
urn:nbn:de:gbv:3:2-116319
Keywords: C22; C52; C53; E37; R11; 330; business surveys; East Germany; MIDAS model; nowcasting